Islamic wealth management in Malaysia: an assessment in the light of Maqasid Al Shariah - Abdul Wahab, Abdul Hamid; Abdul Razak, Dzuljastri (2016)
The consistent growth in Asian region has transformed into a rapid increase in wealth accumulation with the private financial wealth in the region forecasted to grow at 11.4 % cumulative annual rate over the next four years. This is expected to reach approximately US $48 trillion by 2017. This massive and growing pool of wealth signifies a substantial prospect for the asset management sector in Malaysia. Accordingly, the development of a vibrant wealth management industry in Malaysia consistent with the doctrines of Islam could go a long way towards enhancing inclusiveness and sustainability in the financial sector. As a new discipline of Islamic finance, Islamic wealth management is seen as the best alternative to cater to this need. This study presents an overview about the framework of Islamic wealth management in accordance with the principles of Maqasid Al Shariah